36.3k views
3 votes
How do I do this qn?

How do I do this qn?-example-1

1 Answer

2 votes
You can take the log of the left and right hand side, and then apply the logarithm rules:

log(aˣ) = x·log(a)
log(ab) = log(a) + log(b)

log(9^(x-1) * 2^(2x+2)) = log(6^(3x))
log(9^(x-1)) + log(2^(2x+2)) = 3x log(6)
(x-1) log(9) + (2x+2) log(2) - 3x log(6) = 0
x(log9 + 2log2 - 3log6) = log9 - 2log2
x = (log9 - 2log2) / (log9 + 2log2 - 3log6)

simplifying by writing log9 = 2log3 and log6 = log2+log3

x= 2(log3 - log2) / (2log3 + 2log2 - 3log2 - 3log3) =
x= -2(log3 - log2) / (log3 + log2) = -2 log(3/2) / log(6)

So 6^x = 4/9
User Shaahiin
by
7.6k points